LO49: Digital technology distraction for acute pain in children: a meta-analysis. (May 2020) - Gates, M.; Hartling, L.; Shulhan-Kilroy, J.; MacGregor, T.; Guitard, S.; Wingert, A.; Featherstone, R.; Vandermeer, B.; Poonai, N.; Kircher, J.; Perry, S.; Graham, T.; et al.
Abstract : Introduction: Digital distraction is being integrated into pediatric pain care, but its efficacy is currently unknown. We conducted a systematic review to determine the effect of digital technology distraction on pain and distress for children experiencing acutely painful conditions or medical procedures. Methods: We searched eight online databases (MEDLINE, Embase, Cochrane Library, CINAHL, PsycINFO, IEEE Xplore, Ei Compendex, Web of Science), grey literature sources, scanned reference lists, and contacted experts for quantitative studies where digital technologies were used as distraction for acutely painful conditions or procedures in children. Study selection was performed by two independent reviewers with consensus. One reviewer extracted relevant study data and another verified it for accuracy. Appraisal of risk of bias within studies and the certainty of the body of evidence were performed independently in duplicate, with the final appraisal determined by consensus. The primary outcomes of interest were child pain and distress. Results: Of 3247 unique records identified by the search, we included 106 studies (n = 7820) that reported on digital technology distractors (e.g., virtual reality; videogames) used during common procedures (e.g., venipuncture, minor dental procedures, burn treatments). We located no studies reporting on painful conditions. For painful procedures, digital distraction resulted in a modest but clinically important reduction in self-reported pain (SMD -0.48, 95% CI -0.66 to -0.29, 46 RCTs, n = 3200), observer-reported pain (SMD -0.68, 95% CI -0.91 to -0.45, 17 RCTs, n = 1199), behavioural pain (SMD -0.57, 95% CI -0.94 to -0.19, 19 RCTs, n = 1173), self-reported distress (SMD -0.49, 95% CI -0.70 to -0.27, 19 RCTs, n = 1818), observer-reported distress (SMD -0.47, 95% CI -0.77 to -0.17, 10 RCTs, n = 826), and behavioural distress (SMD -0.35, 95% CI -0.59 to -0.12, 17 RCTs, n = 1264) compared to usual care. Few studies directly compared different distractors or provided subgroup data to inform applicability. Conclusion: Digital distraction provides modest pain and distress reduction for children undergoing painful procedures; its superiority over non-digital distractors is not established. Healthcare providers and parents should strongly consider using distractions as a pain-reduction strategy for children and teens during common painful procedures (e.g., needle pokes, dental fillings). Context, child preference, and availability should inform the choice of distractor.